Inter- and intra-observer variability in Sonographic measurements of the cross-sectional diameters and area of the umbilical cord and its vessels during pregnancy - Marussi Emilio F; Souza Carla E; Cecatti Jose G; Barbieri Cristiane; Costa Jose V (BMC, 2008)
Abstract Background The purpose of the study was to evaluate inter- and intra-observer variability in sonographic measurements of the cross-sectional area of the umbilical cord and the diameters of its vessels in low-risk pregnancies of 12 to 40 weeks of gestation. Methods A prospective cross sectional study was performed in 221 pregnant women at different gestational ages. Measurements were carried out also by a second observer to evaluate inter-observer variability and repeated once again by the first observer to assess intra-observer variability. The linear correlation between the measurements (Spearman's coefficient of correlation) and their reliability through the intraclass correlation coefficient (ICC), the Cronbach's alpha coefficient and the limits of agreement proposed by Bland and Altman were evaluated. Results The results showed that inter-observer and intra-observer variability did not show any significant difference between examiners. A good linear correlation between the measurements and reliability was obtained, with values of R, ICC and Cronbach's alpha all above the standard limits. Conclusion It is possible to conclude that inter- and intra-observer variability in the measurements of the umbilical cord and its vessels was small; their reliability and agreement were good.